Recruiting dental practices for research: insights from a practice-based trial in Germany - Hennrich, Patrick; Fehrer, Valeska; Müller, A. L.; Daniels-Stumpf, J.; Jepsen, Søren; Listl, Stefan (JDR clinical & translational research, 2025)
Background: While the relevance of implementation research in dentistry is increasingly emphasized, practice-based trials are still relatively uncommon in dental research. Despite being critical for successful practice-based research, little is known about the recruitment of dental professionals to participate in practice-based trials. Against this background, the purpose of this study was to extract key learnings about the opportunities and challenges for recruiting dental practices from a large-scale practice-based trial in Germany. - Methods: Leveraging quantitative and qualitative methods, participation rates of dental practices and experiences of researchers involved in a large-scale trial in German dental practices were examined. Quantitative analyses focused on the rate of practices that initially expressed interest to participate in the trial, the rate of practices that subsequently gave informed consent to participate in the trial, and variations in participation by different modes of invitation for the study. Qualitative data from dental practices and a focus group with the research coordinators were analyzed by means of thematic analysis, focused on drivers and barriers for practices to participate in the trial. - Results: Of 6,840 invited practices, 287 (4.2%) practices indicated their interest and 159 (2.3%) participated. The mode of invitation was significantly associated with participation (p < 0.05). The practices’ reasons for nonparticipation included shortage of staff and time to adequately integrate the study processes into practice workflows. The research coordinators also identified a lack of established practice-based research networks in dentistry. - Discussion: While practice-based research is key to driving positive change in oral health systems, the findings of this study suggest considerable barriers for recruiting dental practices to participate in research. Understanding the mechanisms through which participation rates can be increased is crucial for the successful operationalization of practice-based research in dentistry. Implementation-oriented research in dentistry would benefit substantially from enhancements of practice-based research networks. - Trial Registration: The underlying project was registered prospectively on July 3, 2023, at the German Clinical Trials Register (www.drks.de) under ID DRKS00030587. - Knowledge Transfer Statement: The results of this study can be used by clinicians and clinical researchers when planning practice recruitment for practice-based trials. This could allow for more precise sample size planning and ultimately contribute to improved patient health through the increased validity of studies.